Prevalence of Hyperprolactinemia in Overt and Subclinical Hypothyroidism at a Tertiary Center in Basra, Iraq - Aya Al-Rubaye; Nassar Alibrahim (Al-Anbar Medical Journal, 2025)
Background: Hyperprolactinemia is a common condition resulting from excessive prolactin secretion by pituitary lactotrophs. Both overt and subclinical hypothyroidism (ScH) contribute to its development.Objectives: To assess the prevalence of hyperprolactinemia in patients with subclinical and overt hypothyroidism and explore its association with polycystic ovary syndrome (PCOS) and body mass index (BMI).Materials and Methods: This retrospective cross-sectional study included 917 women who underwent thyroid function and serum prolactin testing at Faiha Specialized Diabetes, Endocrine, and Metabolism Center in Basra between 2017 and 2023. Patients were categorized into euthyroid, ScH, and overt hypothyroidism based on thyroid-stimulating hormone (TSH) and free tetra-iodothyronine (FT4) levels. Hyperprolactinemia was defined as serum prolactin ≥ 20 ng/mL.Results: The prevalence of hyperprolactinemia was 24.2%, with higher rates in ScH (36.1%) and overt hypothyroidism (35.9%) compared to the euthyroid group (21.7%). The median TSH levels were significantly higher in overt hypothyroidism than in ScH and euthyroid groups, while FT4 levels were significantly lower in overt hypothyroidism. PCOS was observed in 15.4% of participants, with no significant association with thyroid dysfunction. However, PCOS patients had significantly higher prolactin levels than non-PCOS patients. A moderate positive correlation was observed between TSH and prolactin levels in overt hypothyroidism, while no significant correlation was found in ScH.Conclusions: Prolactin levels were significantly elevated in subclinical and overt hypothyroidism, emphasizing the need for prolactin assessment in these patients. PCOS patients exhibited higher prolactin levels. Future community-based assessments can strengthen these findings.